Pemilihan Kepala Daerah Secara Langsung: Solusi atau Masalah? - Warsito Utomo (Unisia, 2004)
The success of general election either is carried out in direct system or Indirect system, will be determined by all of election components such as society, politic al elites and power elites. The elections is the instrument of democracy to reach the good governance to achieve the good society, state and regional autonomy. The direct presidential election will show that people choice is the manifestation of soveregnity of the people to determine who will be the chief of the nation. In the modern democracy. The most important aspect of the integration of nation is constitution. The presidential direct election is just one the mechanisme to measure how good the democration  system run.